The Huns and South Pannonia - Gračanin, Hrvoje (2006)
On the basis of late antique sources and the relevant historiographic literature, this paper lays out a systematic analysis of testimonies regarding the presence of Huns in South Pannonia and the role the Huns had in the disintegration of the Late Roman administrative organization in the Croatian historical area. Special attention is paid to the main features and effects of the Hun rule in Southpannonian provinces of the Later Roman Empire. The paper also deals with the issue of the extent of impact the Huns had on the changes in the relations between the East and the West at that time in respect of Westillyrian region.
Projekt MZOS
ENG